The myth of responsiveness. Discourse analysis on the indirect effectiveness of building orders and planning-law expropriations - Kolocek, Michael; Hengstermann, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Building orders and planning-law expropriations are viewed as particularly interventionist instruments of the Federal Building Code. The two instruments share another characteristic in addition to this high degree of interventionism, namely that they are rarely used in practice. This is due to the theory of responsive land policy, which suggests that less interventionist instruments should be applied first. However, these latter instruments are effective because all those involved, and particularly the affected parties, are aware of the existence of the more intensive options. Municipal decision-making instances thus profit from the provision of building orders and, in particular, expropriation as the ‘ultima ratio’ of planning law. The responsive approach is nonetheless only possible when those affected are aware of, or are made aware of, the existence of the more interventionist instruments. This article presents the results of a discourse analysis of 300 newspapers from the past 25 years. The analysis investigates the hypothesis that the decision-making instances mention building orders and expropriation in these media so as to exercise indirect influence in advance, and thus attempt to persuade those involved to cooperate. The analysis shows that the municipalities also use the local media to consider the use of building orders and expropriation. Often the actual application of the instruments is relativised in the same article by other decisions (for instance by the opposition), independent experts or editorial comments.
Keywords: Housing Policy; Responsive land policy; Building order; Urban expropriation; Discourse analysis; Planning law